La ciudad de los monos Roberto Brenes Mesén, los católicos heredianos y el conflicto cultural de 1907 en Costa Rica - Molina Jiménez, Iván (Editorial Universidad Nacional (EUNA), 2002)
In 1907, the city of Heredia became the epicenter of the most important religious conflict experienced by Costa Rica in the 20th century. A complaint that the theory of evolution was being taught in the Lyceum (i.e. secondary school) of that city, triggered an increasingly intense confrontation between the Catholic parishioners and the circle of young radical intellectuals articulating around the writer and educator Roberto Brenes Mesén. In the course of this process, Costa Rican society, to the alarm of the government of Cleto González Víquez, was the scene of popular mobilizations in defense of the faith, excommunications and burning of impious texts, while Catholic morality was systematically questioned based on sexual abuse attributed to priests. For a moment, it seemed that the country had gone back in time, and that the ghosts of 1884 were present.